Paramoguai kavieng, a new genus and species of camptandriid crab from Papua New Guinea (Crustacea: Brachyura) - Ahyong, Shane T. (Zootaxa, 2014)
Paramoguai kavieng is recognised as a new genus and species of camptandriid crab, recently discovered in Papua New Guinea. The new genus closely resembles Moguai Tan & Ng, 1999, from the western Pacific, sharing similar carapace and pereopod structure, but is distinguished chiefly by the fusion of the maxilliped 3 ischiomerus, features of the epistome and front, and position of the anterolateral margins of the carapace. The new genus is unique in the Camptandriidae Stimpson, 1858, in having an epistome with a bilobed buccal margin. Moguai pyriforme Naruse, 2005, from Japan, which differs from P. kavieng primarily in carapace ornamentation and gonopod morphology, is transferred to Paramoguai.